Evaluasi Suplementasi Indigofera zollingeriana Sebagai Sumber Green Protein concentrate Terhadap Produksi Gas Metan, Amonia dan Sintesis Protein Mikroba Rumen - Afzalani Afzalani; R.A Muthalib; Rahmi Dianita; Fachroerrozi Hoesni; Raguati Raguati; Endri Musnandar (Universitas Batanghari Jambi, 2021)
The use of protein with low-cost, high quality, low methane, and ammonia emissions are a prerequisite as a protein source in ruminant. However, the European Commission has prohibited protein derived from fish meals for ruminant feeds. So encouraging efforts to explore the other protein sources to be most important. Most of the high protein legumes grow in tropical areas such as Indonesia and have the potential as an alternative protein source in ruminant feed, including Indigofera zollingeriana (25-27% protein content). But many browse legumes with high protein are a heterogeneous group of plants, with variable secondary metabolic content and rumen degradable protein. The aim of this experiment was to evaluate the characteristics fermentation of IZ as green protein supplement on in vitro methane, ammonia and microbial protein production. The experiment was a completely randomized design with four different level supplementation of Indigofera zollengeriana (IZ) as green protein concentrate and five replications. The treatment diets were R0; basal diet (60% forage + 40% concentrate) + 0% IZ, R1; R0 + 10% IZ, R2; R0 + 20% IZ, and R3; R0 + 30% IZ. The experiment result showed that supplemenatation of IZ was significant effects (P<0.05) to increase total gas, ammonia (N-NH3), total volatile fatty acid (TVFA), and metabolizable energy (ME) and significant effect (P<0.05) to decrease of methane and methane percentage. Supplementation IZ at a level of 10% was significantly higher for dry matter digestibility (DMD), organic matter digestibility (OMD), and microbial protein production (PPM) than diets treatment of R0, R2, and R3. The experiment concluded that Supplementation of I. zollingeriana (IZ) was able to reduce the methane gas production. Protein characteristics of IZ have easily degradable by rumen microbe showed the ammonia production was linearly increasing by 45.66% for each increasing level of IZ supplementation. Microbial protein production was higher (184.33 mg/ml) obtained of IZ supplementation up to 10% (R1). The experiment suggests doing protected protein of IZ when be used as a protein source in ruminant diets.